Southern right whale (Eubalaena australis) calf mortality at Península Valdés, Argentina: Are harmful algal blooms to blame?. Issue 2 (4th September 2015) - Wilson, Cara; Sastre, A. Viviana; Hoffmeyer, Monica; Rowntree, Victoria J.; Fire, Spencer E.; Santinelli, Norma H.; Ovejero, Soledad Díaz; D'Agostino, Valeria; Marón, Carina F.; Doucette, Gregory J.; Broadwater, Margaret H.; Wang, Zhihong; et al.
Abstract: Península Valdés (PV) in Argentina is an important calving ground for southern right whales (SRWs, Eubalaena australis ). Since 2005, right whale mortality has increased at PV, with most of the deaths ( 90%) being calves <3 mo old. We investigated the potential involvement of harmful algal blooms (HABs) in these deaths by examining data that include: timing of the SRW deaths, biotoxins in samples from dead SRWs, abundances of the diatom, Pseudo‐nitzschia spp., and the dinoflagellate, Alexandrium tamarense, shellfish harvesting closure dates, seasonal availability of whale prey at PV and satellite chlorophyll data. Evidence of the whales' exposure to HAB toxins includes trace levels of paralytic shellfish toxins (PSTs) and domoic acid (DA) in tissues of some dead whales, and fragments of Pseudo‐nitzschia spp. frustules in whale feces. Additionally, whales are present at PV during both closures of the shellfish industry (due to high levels of PSTs) and periods with high levels of Pseudo‐nitzschia spp. and A. tamarense . There is a positive statistical relationship between monthly Pseudo‐nitzschia densities (but not A. tamarense ) and calf deaths in both gulfs of PV.